Real-time estimation of 3D human arm motion from markerless images for human-machine interaction - Verma, S.; Kofman, J. (Proceedings of SPIE, 2003)
Vision-based motion tracking is commonly used in surveillance, human-machine interfaces in robotics and automation, virtual and augmented reality applications and biomechanics. Most techniques require markers, use a predefined motion sequence or user-intervention for initialization, and do not process in real-time. This paper describes the implementation of a vision-based non-invasive technique for markerless real-time tracking of human-arm motion. Human-arm motion is tracked by processing images from two calibrated cameras in real-time to estimate the position of the 3D joint centers of the wrist and elbow, and determine the orientation of the hand from the 3D positions of the index finger and thumb. Tracking of the hand and arm was carried out without any prior knowledge of subject's arm length, texture, width and distance from the camera.